Comparison of Intra-Operative Hemorrhage by Blunt and Sharp Expansion of Uterine Incision at the Cesarean Section (Medical Forum Monthly, 2024)
Objective: To compare the mean drop in hemoglobin in patients undergoing cesarean section in blunt versus sharp uterine incision.Study Design: Randomized controlled trial.Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynecology, Lady Aitchison Hospital, Lahore from June 2017 to December 2017.Materials and Methods: One hundred patients are divided into two groups undergoing lower segment caesarean section through pfannenstiel incision.50 patients are randomized to blunt incision group and 50 patients to sharp incision group.Results: Indications for cesarean sections and maternal demographic factors were similar in both groups and significant fall in hemoglobin seen between two groups. Hemoglobin fall in sharp uterine incision is more as compared to blunt uterine incision and the difference between the groups is statistically significant. Mean Hemoglobin fall was 0.79±0.19 in group A versus 1.21±0.19 in group B. The difference was statistically significant among 2 groups p value=0.00(<0.05)Conclusion: In lower segment cesarean section less hemoglobin fall noticed in blunt uterine incision as compared to sharp group so blunt expansion of uterine incision is better than sharp incision.